On the origins of Balkan endemics: the complex evolutionary history of the Cyanus napulifer group (Asteraceae) - Olšavská, Katarína; Slovák, Marek; Marhold, Karol; Štubňová, Eliška; Kučera, Jaromír (Annals of botany, 2016)
BACKGROUND AND AIMS: The Balkan Peninsula is one of the most important centres of plant diversity in Europe. Here we aim to ﬁll the gap in the current knowledge of the evolutionary processes and factors modelling this astonishing biological richness by applying multiple approaches to the Cyanus napulifer group. METHODS: To reconstruct the mode of diversiﬁcation within the C. napulifer group and to uncover its relationships with potential relatives with x = 10 from Europe and Northern Africa, we examined variation in genetic markers (amplified fragment length polymorphisms [AFLPs]; 460 individuals), relative DNA content (4',6-diamidino-2-phenylindole [DAPI] flow cytometry, 330 individuals) and morphology (multivariate morphometrics, 40 morphological characters, 710 individuals). To elucidate its evolutionary history, we analysed chloroplast DNA (cpDNA) sequences of the genus Cyanus deposited in the GenBank database. KEY RESULTS: The AFLPs revealed a suite of closely related entities with variable levels of differentiation. The C. napulifer group formed a genetically well-defined unit. Samples outside the group formed strongly diversified and mostly species-specific genetic lineages with no further geographical patterns, often characterized also by a different DNA content. AFLP analysis of the C. napulifer group revealed extensive radiation and split it into nine allopatric (sub)lineages with varying degrees of congruence among genetic, DNA-content and morphological patterns. Genetic admixture was usually detected in contact zones between genetic lineages. Plastid data indicated extensive maintenance of ancestral variation across Cyanus perennials. CONCLUSION: The C. napulifer group is an example of a rapidly and recently diversified plant group whose genetic lineages have evolved in spatio-temporal isolation on the topographically complex Balkan Peninsula. Adaptive radiation, accompanied in some cases by long-term isolation and hybridization, has contributed to the formation of this species complex and its mosaic pattern.
Keywords: Balkan Peninsula; Asteraceae; Amplified Fragment Length Polymorphism Analysis; analýza polymorfismu délky amplifikovaných restrikčních fragmentů; biodiverzita; genetické markery; biologická evoluce; Biological Evolution; Balkánský poloostrov; DNA chloroplastová; Flow Cytometry; průtoková cytometrie; Biodiversity; DNA, Chloroplast; Genetic Markers